LA DECENTRALISATION COMME MODE DE GOUVERNANCE DE LA CHOSE PUBLIQUE EN REPUBLIQUE DEMOCRATIQUE DU CONGO ANALYSE CRITIQUE SUR L’ARSENAL JURIDIQUE - TSHINKENKA, Evariste NSUMBU; MWAIKENGA, Marie BWASA (IJRDO - Journal of Social Science and Humanities Research, 2021)
Decentralisation is the opposite of centralisation. This opposition is absolute only in terminology and theory, but in practice these notions are only relative to reality. A state is never fully decentralised, which means that there are decentralised territorial entities and decentralised entities. Decentralisation is not a recent concept, it is according to the little redhead a system of organisation of the administrative structures of the state which grants decision making and management powers to regional or local automous bodies. The centralising form which has long marked the territorial administration in the Democratic Republic of Congo has not made it possible to associate a harmonious development policy. Territorial decentralisation confers autonomy on autonomous local authorities but which are subject to state control. It supposes the existence of a geographically determined fraction of the territory. Territorial decentralisation is there fore a management process which consists on the one hand is distributing decision-making powers over administrative missions between the central autorities and the local authorities elected at the head of the public authorities created by the state and others to transfer the management of all local interests to these communities endowed with legal personality and management autonomy vis-à-vis the central power. From this point of view, it turned out egoism, corruption, embezzlement, impunity, the non-involvement of the population in constitutes a major obstacle to good governance and the development of territorial entities, decentralized territorial entities of real legal persons distinct from the state but under its supervision, centers of impetus for powers and decisions, protectors of solving local problems of a political, economic, social and culturel nature with the aim of achieving development objectives.